Praktek Perjanjian Bagi Hasil Tanah Pertanian Antara Petani Pemilik Dengan Petani Penggarap Di Desa Gondosuli, Kecamatanpakuniran, Kabupaten Probolinggo: (Yuridis Empiris) - Fathul Qorib; Muhammad Zainal (JUSTNESS - Jurnal Hukun dan Agama, 2021)
Basically, the State of Indonesia is an agrarian country, where the land can be planted with any crops, therefore the author takes the title "Practice of Agricultural Land Production Sharing Agreements Between Owner Farmers and Cultivators in Gondosuli Village, Pakuniran District, Probolinggo Regency" which is directly related to the agreement. profit sharing from agricultural land in Gebangan Village. In writing this thesis, the author raised three problems, namely: (1). What are the Procedures, Forms and Amounts of the Profit Sharing Coefficient of Agricultural Land in Gebangan Village. (2). How are the Efforts to Improve the Fate of the Farmers in relation to the Procedures, Forms and Coefficients for Sharing Agricultural Land Yields in Gebangan Village. (3). Who usually mediates when there is a problem between the Owner Farmer and the Cultivator in Gebangan Village.The purpose of this writing is Special Purpose.Specifically, the goal to be achieved is to know the practice of sharing agricultural land in Gebangan Village, Krejengan District, Probolinggo Regency, including wanting to know the Procedures, Forms and Profit Sharing Coefficients between Owner Farmers and Cultivators, so that in the future it will be known as well. the shortcomings that exist in the implementation of the agreement, so that in the end it will be possible to take steps to improve the future of the Farmers, especially Cultivators. Where the sharecroppers are always oppressed by landowners who have a lot of capital. General PurposeIt is to develop the level of institutional scientific knowledge, in this case Educational Institutions on Campus, including policy makers in the field of Agriculture, especially those relating to efforts to advance the future of Small Farmers in Indonesia, so that with this knowledge they can be used as a guide for updating provisions. there is, with the hope that the lives of the Farmers who are actually very useful for the Indonesian Nation are better and more advanced, so that our nation can be known again as an Agrarian Country.The method of this research is using the Juridical Empirical research method in which the legal sources used are from several valid references and through direct research in the field, where the resource persons have been directly involved in the practice of this profit-sharing agreement. The results of this study are the authors can provide a little knowledge to the people who live in Gebangan Village how the procedure for the correct agricultural land production sharing agreement for owners and cultivators, which is based on Law No. 2 of 1960, the correct agreement must be in writing, there is a witness or make an agreement in front of the local village head so that the legal basis is strong, if there is fraud from one of the parties who made the agreement then it can be brought to justice because they already have strong evidence to be brought to justice, but now there are still many farmers making agreements with just words without making a written agreement so that if there is a problem you can't do anything. Therefore, the government made a law for agricultural land production sharing agreements that occurred between the owner and the cultivator, so that the land owner could not arbitrarily treat the tenant farmers, after being given an understanding of the agreement regulated by Law Number 2 of 1960, in Gebangan Village. have already entered into a written agreement.. Keyword: Constitution, Practice